LET US DANCE TO LIVE: THE INFLUENCE OF AFRO-POP-MUSIC ON PROMOTION OF THE NORMS OF CYBERCRIME AMONG YOUNG PEOPLE IN NIGERIA - OYENUGA, Adedeji; Ajewole, Olamide (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2023)
Music is an integral part of every culture that serves entertainment, cultural transmission, and mood moderation in every society and is enhanced by globalisation and the internet. Beyond these purposes, music has equally been the instrument for transmitting cultural values with high tendencies to positively and negatively affect human behaviour. This study explores how Afro-Pop music promotes the Norms of Cybercrime in Nigeria through the musicians' content, slangs, and personae. The study used cognitive dissonance and constructivism theories to explain how music has influenced youth involvement in Cybercrime. This is an analysis of 25 full songs and 35 other songs with at least one-sentence of cybercrime messages and the use of popular cybercrime slangs. These songs were purposively selected Cybercrime promoting songs that were released between 2007 and 2020. These songs were content-analyzed along with the singers' attributes and achievements in the entertainment world in Nigeria. The study found that contents of cybercrime songs, lifestyle, cybercrime techniques, hard work, resilience and other messages can inspire young people. It also found slangs like Japa, CC, Client, Cashout, and Aza that have become integral parts of daily communication. The majority of these songs were also popular through downloads, award nominations and awards, and others. The study also found that the singers' personalities were worthy of emulation by young individuals in society. As such, music is both functional and dysfunction and a part of the culture inseparable from society members. Therefore, it is crucial for there to be global cooperation in censoring music to reduce its influence on society members, especially the young ones.